2018
DOI: 10.35808/ijeba/165
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Leadership and Organizational Citizenship Behavior: The Mediating Roles of Psychological Empowerment and Emotional Intelligence in Medical Service Industry

Abstract: This study aims to investigate the effect of empowering leadership on organizational citizenship behavior (OCB) through psychological empowerment and emotional intelligence. After analyzing 125 sets of the employee for collecting data in the medical service industry of Jepara district-Indonesia, this study found that empowering leadership was related to OCB. In addition, this study further found that psychological empowerment and emotional intelligence served as significant mediating in the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…Similarly, extant literature supports the findings of H2a and H2b (e.g. Akgunduz and Bardakoglu, 2017; Joo and Jo, 2017; Kim and Fernandez, 2017; Saleem et al , 2017; Shahab et al , 2018; Singh and Singh, 2019; Wilutantri and Etikariena, 2017). The mediating role of psychological empowerment in the relationship between transformational leadership and employee outcomes (turnover intention and OCB) are also significant.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, extant literature supports the findings of H2a and H2b (e.g. Akgunduz and Bardakoglu, 2017; Joo and Jo, 2017; Kim and Fernandez, 2017; Saleem et al , 2017; Shahab et al , 2018; Singh and Singh, 2019; Wilutantri and Etikariena, 2017). The mediating role of psychological empowerment in the relationship between transformational leadership and employee outcomes (turnover intention and OCB) are also significant.…”
Section: Discussionsupporting
confidence: 73%
“…For example, several studies concluded that OCB influenced by knowledge management (Lin & Hsiao, 2014) and empowerment (e.g. Yangaiya & Abubakar, 2015;Cheasakul & Varma, 2016;Goksoy, 2017;Shahab, Sobari & Udin, 2018;Jayarathna, 2019;Tindowen, 2019). As a consequence of this evidence, school leaders urgent to manage knowledge management and empowerment better through various policies, approaches, methods, and strategies that are relied on to develop the teacher's OCB.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators if in good condition can increase OCB manifested in altruism, conscientiousness, sportsmanship, courtesy, and civic virtue (Arifin, Herri, & Puteri, 2019). Several studies carried out by Yangaiya and Abubakar (2015), Cheasakul and Varma (2016), Goksoy (2017), Shahab, Sobari, and Udin (2018), Jayarathna (2019), and Tindowen (2019) also revealed that empowerment influences OCB. Based on the statements and studies above, the first hypothesis in this study is: H2: Empowerment had a direct effect on OCB.…”
Section: Empowerment and Ocbmentioning
confidence: 93%
“…OCB influences employee performance because it includes a strong conviction that OCB is essential to organizational success (Basu, Pradhan, and Tewari 2017;Hermawati and Mas 2017), (Dong & Phuong, 2018). Empirical results indicate that OCB implants a public service ethic (Rayner, Lawton, & Williams, 2012), diminishes clashes between the employees (Beheshtifar & Hesani, 2012), and develops performance of the employee (Asiedu, Sarfo, & Adjei, 2014;Darsana, 2013;Harwiki, 2013;Maharani, Troena, & Noermijati, 2013;Putri, Udin, & Djastuti, 2019;Shahab, Sobari, & Udin, 2018;Suwanti & Udin, 2020).…”
Section: Ocb (Organizational Citizenship Behavior)mentioning
confidence: 99%